Risk of premenopausal breast cancer in association with occupational exposure to polycyclic aromatic hydrocarbons and benzene - Petralia, SA; Vena, JE; Freudenheim, JL; Dosemeci, Mustafa; Michalek, A; Goldberg, MS; Brasure, J; Graham, S (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'This study examined the relationship between risk of premenopausal breast cancer and occupational exposure to benzene and polycyclic aromatic hydrocarbons (PAH) and whether the proposed relationship between PAH and breast cancer differed by tumor estrogen receptor (ER) status.' ' METHODS ': 'In a case-referent study of premenopausal breast cancer, occupational histories and other information were obtained through interviews, and job-exposure matrices were used to assess exposure to PAH and benzene.' ' RESULTS ': 'A dose-response relationship for the probability of exposure to benzene [low: odds ratio (OR) 1.64, 95% confidence interval (95% CI) 0.64-4.21; high: OR 1.95, 95% CI 1.14-3.33) and to PAH (low: OR 1.56, 95% CI 0.78-3.12; high: OR 2.40, 95% CI 0.96-6.01). Risk increased with duration of exposure to benzene, but not to PAH. A dose-response relationship was not evident for the intensity of exposure to benzene or to PAH. When analyses were stratified by tumor ER status, PAH exposure was related to a greater increase in the risk of ER-positive (OR 2.27, 95% CI 1.14-4.54) than ER-negative (OR 1.12, 95% CI 0.47-2.64) breast cancer. Risk of ER-positive, but not ER-negative, tumors increased with the probability of exposure to PAH.' ' CONCLUSION ': 'The findings suggest an association between risk and occupational exposure to benzene. Although it was difficult to study PAH independently of benzene, there was some suggestion of an association between PAH exposure and ER-positive tumors. These data should be interpreted with caution because of the limitations of this study, including low-response rates and small numbers of exposed persons.
Keywords: benzene; estrogen receptor; occupational exposure; polycyclic aromatic hydrocarbon; premenopausal breast cancer; woman